2014
DOI: 10.4172/2161-0959.1000191
|View full text |Cite
|
Sign up to set email alerts
|

Blast from the Past-using PTH to Differentiate Acute versus Chronic Kidney Disease

Abstract: In these times of limited financial and human resources, physicians must be cognizant of the rising costs of healthcare. Expensive imaging studies should be reserved for conditions that are particularly challenging to diagnose using traditional laboratory tests. Consequently, we must revisit the use of alternative simple, inexpensive and readily available laboratory tests to help differentiate medical conditions. Therefore, we would like to revisit the use of intact PTH as a discriminatory lab value in evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Cavayero et al [17] described a small case series, 6 patients with elevated serum creatinine, AKI-4 and CKD-2 who had serum iPTH levels assayed. They concluded that iPTH was an inexpensive and readily available marker for differentiating AKI from CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Cavayero et al [17] described a small case series, 6 patients with elevated serum creatinine, AKI-4 and CKD-2 who had serum iPTH levels assayed. They concluded that iPTH was an inexpensive and readily available marker for differentiating AKI from CKD.…”
Section: Discussionmentioning
confidence: 99%